2021
DOI: 10.1080/01419870.2021.1928254
|View full text |Cite
|
Sign up to set email alerts
|

Is intersectional racial justice organizing possible? Confronting generic intersectionality

Abstract: This article empirically charts how a discursive construction of the separation of race and racial justice organizing, and "intersectionality" serves to uphold white supremacy and efface intersectional marginalization among people of colour. Undertaking the first study of how UK policymakers and practitioners in equality organizations understand and operationalize "intersectionality", it maps "generic intersectionality", which is delivered to benefit "all". Through empirical examples, its detrimental effects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A conspicuous silence exists around the way scholars steeped in white feminism tend to co-opt, dilute, and de-radicalise anti-racist and decolonial epistemologies developed by Black, Indigenous, and (Bilge, 2013;Liu, 2018). Academic discourse, of the feminist variety too, is characterised by epistemologies of ignorance (Mills, 1997;Tate and Page, 2018) that deny the white supremacy at work in the uptake, genericisation, (mis)application, and subsequent critique of what was once an explicitly Black feminist theory (Christoffersen, 2022;May, 2014). Through this process, intersectionality has been sanitised and made more attractive and approachable, for claiming it seems to offer mainstream (white middle-class) feminism a security blanket against accusations from Black feminists of racism, from queer and trans feminists of cis-heterosexism, or from Marxist feminists of ignorance of class analysis.…”
Section: Feminist Theory Building On Intersectionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…A conspicuous silence exists around the way scholars steeped in white feminism tend to co-opt, dilute, and de-radicalise anti-racist and decolonial epistemologies developed by Black, Indigenous, and (Bilge, 2013;Liu, 2018). Academic discourse, of the feminist variety too, is characterised by epistemologies of ignorance (Mills, 1997;Tate and Page, 2018) that deny the white supremacy at work in the uptake, genericisation, (mis)application, and subsequent critique of what was once an explicitly Black feminist theory (Christoffersen, 2022;May, 2014). Through this process, intersectionality has been sanitised and made more attractive and approachable, for claiming it seems to offer mainstream (white middle-class) feminism a security blanket against accusations from Black feminists of racism, from queer and trans feminists of cis-heterosexism, or from Marxist feminists of ignorance of class analysis.…”
Section: Feminist Theory Building On Intersectionalitymentioning
confidence: 99%
“…Nonetheless, critical engagement with the politics of reading, interpretation, and reception of intersectionality (e.g., Bilge, 2013;Cho et al, 2013;Christoffersen, 2022;Collins, 2019;May, 2014;Nash, 2015) offers valuable insights for the study of inequalities in entrepreneurship. Such scholarship outlines intersectionality's transformative function within women's, gender, and feminist studies: disruptive of essentialist, binary, and white feminism, intersectionality formally amplified Black feminism and theory, which was historically marginalized, co-opted, and disappeared within the academy (Collins, 2019;May, 2014;Nash, 2019), enabling a paradigmatic shift that challenged traditional Eurocentric and masculinist notions of research methodology (Hancock, 2007).…”
Section: Feminist Theory Building On Intersectionalitymentioning
confidence: 99%
“…A wide and deep body of scholarship and testimony now exists that encompasses experiences and perspectives at the intersection of disability, sexuality, racialisation, gender, colonialism, and other systems of socio-political structural power. This has sometimes taken the form of personal accounts and testimony, of academic research, of political writing, and of activist work, or some combination thereof, among other modes (see for example Christoffersen, 2020Christoffersen, , 2021Hill Collins, 2019). UK equality legislation itself recognises that discrimination can be experienced on more than one axis and simultaneously (see section 14 of the EqA)though, as drafted, it only refers to two combined protected characteristics listed therein, including race, sex, gender reassignment and sexual orientation.…”
Section: Accounting For Intersectionalitymentioning
confidence: 99%
“…This is the antithesis of Crenshaw's original idea, and renders the existence and impact of intersectional discrimination less visible. This may be particularly problematic in the context of racial justice, as Christoffersen saw in her ethnographic research examining how equality organisations were ‘doing’ intersectionality: she found that implementation of a more ‘generalised’ intersectional practice across the 9 protected characteristics of the EqA ‘whitens’ the concept of intersectionality, and can in fact ‘uphold white supremacy and efface intersectional marginalization among people of colour’ (2021: 1). The ‘othering’ that can occur through this process embeds rather than challenges marginalisation.…”
Section: Accounting For Intersectionalitymentioning
confidence: 99%
“…Why was gender equality legislation designed in such a way that it mainly benefitted white and otherwise relatively privileged women? Given that UK anti-discrimination legislation initially addressed race, how did gender, which came later, achieve the primacy perceived by many working in equalities decades later (Christoffersen, 2022a)? And what discourses were at work in these processes?…”
Section: Introductionmentioning
confidence: 99%